Biomarkers to optimize PSMA-targeted radioligand therapy for metastatic castration-resistant prostate cancer - Beltran, Himisha; Calais, Jeremie; Emmett, Louise; Kuo, Phillip H.; Logothetis, Christopher J. (Frontiers in Oncology, 2025)
Although the recently approved prostate-specific membrane antigen (PSMA)-targeted radioligand therapy (RLT) [177Lu]Lu-PSMA-617 has improved outcomes for patients with metastatic castration-resistant prostate cancer (mCRPC), not all patients respond optimally to this treatment; even measuring response accurately can be difficult. Moreover, there is currently a lack of validated prognostic and predictive biomarkers for [177Lu]Lu-PSMA-617 treatment in this patient population. There is, therefore, a growing need to identify biomarkers to help optimize patient selection for [177Lu]Lu-PSMA-617 and guide therapy decision-making. This review explores the landscape of emerging clinical, molecular, and imaging biomarkers, and their potential utility as prognostic and/or predictive biomarkers in the context of [177Lu]Lu-PSMA-617 treatment for patients with mCRPC.